Sound identification in the swiftlet house - Aida Shafina, Shofi (2012)
Swiftlets farming industry has the potential to grow into a multi-million ringgit industry due to the market demanding on using edible birds‟ nests as base materials for producing natural and organic health supplement products. To encourage the Swiftlets making more nests, their cave-like house should have a great sound identity to make them stay convenient and permanently in that building as if they are in caves. Therefore, it is very important to discover the vocalization of the Swiftlet chirps and mating sounds before being played in the cave-like building. The characteristics of recorded sound will be analyzed using the Sound Analysis Pro (SAP 2011) software. The software will display a desired waveform and the sound will be analyzed based on several featured such as Wiener entropy, pitches, frequency modulation and spectral continuity. The final product is the identification of desired sound that may attract more Swiftlets to make nests in the cave-like building. This will encourage more Swiftlets to mate, play and stay permanent in the areas that have a desired quality of sound as they interest.